Adaptive‐biased sense‐FET–based inductor‐current sensor for 10‐MHz buck converter. (19th February 2020) - Zhou, Yong; Lin, Xiaohui; Yang, Jianxin; Zheng, Yanqi; Leung, Ka Nang
Summary: A sense field effect transistor (FET)–based inductor‐current sensor for buck converters is introduced in this paper. The proposed current sensor adopts and realizes piecewise‐linear adaptive bias to maintain consistent bandwidth and phase margin in the sensor's control loop throughout a wide range of load currents. Moreover, the specially designed turn‐on/off process of switches is introduced together with the sole gain–boosted amplifier to avoid the sharp transitions in the sensed peak and valley currents during the deadtime zone of synchronous buck converters. Simulation results of the proposed sensor show an 11.6‐dB rise in direct current (DC) gain at light load (approximately 200 mA) and 21° improvement in phase margin at heavy load (approximately 2 A), compared with the traditional structure with fixed‐bias current. Furthermore, the variation in the unity gain bandwidth of the proposed structure across the whole load range is 12.8 times lower than that of the traditional designs. Abstract : A sense‐FET–based inductor‐current sensor for buck converters is introduced in this paper. The proposed current sensor realizes piecewise‐linear adaptive bias to maintain consistent bandwidth and phase margin in the sensor's control loop throughout a wide range of load currents. Moreover, the specially designed turn‐on/off process of switches is introduced together with the sole gain–boosted amplifier to avoid the sharp spikes during the mode transitions between sensed peak and valley current signals.